The h200d office: the local embeddedness of the Dutch Crips gang - Roks, R. (Organized crime in the 21st century, 2023)
Based on 3 years of ethnographic research, this chapter departs from the depiction of the h200d - a local neighborhood in the city of The Hague and the home base of the Dutch Crips - as an “office.” Building on the “crime as work” perspective, this metaphor is used to examine the local embeddedness of the Dutch Crips and their criminal activities. First, the usage of the term “office” shows how the local neighborhood serves as a meeting place of gang members but also for partners in crime in need of (criminal) goods, services, or information. Second, the metaphor of the “office” also sheds light on the Crips’ “employees” (gang members), their “business” (criminal activities), and issues related to both the employees and their business endeavors. This case study illustrates that the local embeddedness of the Dutch Crips not only is beneficial for the gang but also hinders their growth and expansion.